The record of the little ice age in the pampean lakes - Laprida, C. (2009)
The Little Ice Age (LIA) is a climate episode between the 16th and middle 19th centuries, characterized in Europe by colder temperatures and occasionally stormy weather. In certain areas of Europe, long instrumental observations record the Little Ice Age partially; however, in the pampean region meteorological data only started about one hundred years ago. The objective of this contribution is to provide new evidences about the Little Ice Age in the Pampean plain based on lake cores. Short cores of Chascomús and Monte lakes were analyzed and, according to AMS data, they span the last 500 years. The Chascomús core consists of three fining upward sequences. Sediment logical and biological proxies demonstrate a benign period from the end of the 15th century. Around 1700 AD lake level decreased and a dry period started and lasted for almost 150 years. After 1850 AD higher lake levels and increased moisture dominate the pampean scenario. The del Monte lake core is also composed of three fining upwards sequences, and AMS chronology assigned a basal age between 1441-1494 AD. Although the model age needs improvement, the events of Chascomús and del Monte lakes seem to be correlated and show coherent regional tendencies of humidity and droughts during the last 500 years.